Integrated Mendelian randomization and single-cell RNA-sequencing analyses identified OAS1 as a novel therapeutic target for erectile dysfunction via targeting fibroblasts - Yi Wang; Guihua Chen; Deng Li (Biology Direct)
Abstract Clinically, phosphodiesterase type 5 inhibitors (PDE5-Is) remain the first-line therapy for erectile dysfunction (ED) patients; however, approximately 35% of these patients are still failing to respond to the therapeutic effects. So, urgent needs are required to identify novel therapeutic targets for ED. Hence, in this report, it was the first time for us to integrate single-cell RNA-sequencing (scRNA-Seq), mendelian randomization (MR) analysis with expression quantitative trait loci (eQTL), and protein quantitative trait loci (pQTL) data to find new treatment targets for ED. Disease-causing changes were revealed by MR analysis, and it showed that the OAS1 eQTL/cis-eQTL/cis-pQTL was causally related to ED, significantly reducing its risks (all P < 0.05). Disease-induced changes were revealed by scRNA-Seq, and it suggested that OAS1 mainly played its role in ED via targeting fibroblasts. We further concluded that the positive regulation of OAS1 gene expression could lead to the vicious circle of ED. As a result, drugs targeting OAS1 in the future might provide more potential opportunities and flexibility for treating ED. In conclusion, our study identified OAS1 as a gene of interest in the context of ED via targeting fibroblasts through integrated MR and scRNA-Seq analyses. While these findings highlighted the potential of OAS1 as a therapeutic target, further experimental and clinical studies were still required to validate its functional role and therapeutic relevance in ED pathology.